EFFECT SPRAY DATES AND CONCENTRATION OF NITROGEN FERTILIZER IN VEGETATVE GROWTH TRAMS PLANTS Melia azedarach L - LATEF, Mohammed FADEL; MUSA, ALI AKRAM; Mahmood, AKRAM SHAKER (Diyala Agricultural Sciences Journal, 2010)
This study was conducted a nursery Department of Horticulture College of Agriculture, University of Tikrit for the period from the beginning of 2007 to the end. The aim of the experiment is to study the effect of spray dated and concentrations of nitrogen fertilization ( 0 , 5 , 10 )g / liter in some of the characteristics of the vegetative growth Melia azadarach seedling . Were calculated Length and stem diameter and number branches and leaves and the surface area . The results showed the the were no significant difference in the dates of spraying all the characteristics studied , Either for fertilizer nitrogen concentrations found there significant differences in the length and stem diameter and surface area and the absence of significant differences between seedling nitrogen fertilizer treatment ( 5 , 10 )g / liter in the character of number of branches and number of leaves , but there are differences between treatments and the treatment of seedlings no fertilizer .